2009
DOI: 10.3748/wjg.15.1472
|View full text |Cite
|
Sign up to set email alerts
|

Primary epithelial tumours of the appendix in a black population: A review of cases

Abstract: AIM:To determine the prevalence, histologic types and clinical features of primary epithelial tumours of the vermiform appendix in a predominantly black population. METHODS:All cases of primary tumours of the appendix identified by review of the histopathology records at the University of the West Indies between January 1987 and June 2007 were selected. Relevant pathologic and clinical data were extracted with supplementation from patient charts where available. Non-epithelial tumours were excluded. The total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
(19 reference statements)
1
10
0
5
Order By: Relevance
“…Although NEN are frequently reported [13], most cases are of an early stage [12,13,14]. The reported incidence has increased in more recent years [1,6]; however, the overall incidence rate is probably roughly within the same range between different races, although some differences have been reported [1,12,15,16,17,18]. Furthermore, common practice in performing appendicectomies may also influence the reported incidence of appendiceal NEN [19,20].…”
Section: Epidemiology and Prognosismentioning
confidence: 93%
“…Although NEN are frequently reported [13], most cases are of an early stage [12,13,14]. The reported incidence has increased in more recent years [1,6]; however, the overall incidence rate is probably roughly within the same range between different races, although some differences have been reported [1,12,15,16,17,18]. Furthermore, common practice in performing appendicectomies may also influence the reported incidence of appendiceal NEN [19,20].…”
Section: Epidemiology and Prognosismentioning
confidence: 93%
“…A possible hormonal influence has not been proven (Graham et al 2009). An epidemiological study from Sweden covering the years showed that, of 5184 NENs, the appendix was the main site of involvement in women, whereas the SI was the main site in men; aNENs showed an unusually early onset with a maximum incidence at age 15-19 years in women and 20-29 years in men (Hemminki & Li 2001).…”
Section: Epidemiologymentioning
confidence: 99%
“…An epidemiological study from Sweden covering the years showed that, of 5184 NENs, the appendix was the main site of involvement in women, whereas the SI was the main site in men; aNENs showed an unusually early onset with a maximum incidence at age 15-19 years in women and 20-29 years in men (Hemminki & Li 2001). Indeed, aNENs are diagnosed at a much younger age of 32-42.2 years (Hemminki & Li 2001, McGory et al 2005, Graham et al 2009, Benedix et al 2010, Turaga et al 2012, Hsu et al 2013 compared to other GI-NENs and all other appendiceal neoplasms, which are diagnosed at an average age of 62.9 and 61.9 years, respectively (Sandor & Modlin 1998). In a large series from The Netherlands, the appendix was the most frequently diagnosed primary site of NENs in patients !35 years (Quaedvlieg et al 2001).…”
Section: Epidemiologymentioning
confidence: 99%
“…Junto con demostrar la presencia o no de infl amación, el estudio histopatológico permite la pesquisa de lesiones neoplásicas apendiculares generalmente inaparentes al examen clínico e imagenológico, siendo su frecuencia reportada en hasta un 0,5% de las apendicectomías [5][6][7][8] ; del mismo modo y en un porcentaje variable permite identifi car elementos parasitarios (Enterobius vermicularis, Entamoeba histolytica, Ascaris lumbricoides, Trichuris trichiura, Schistosoma spp, Taenia spp), asociados o no a infl amación apendicular 1,[9][10][11][12] .…”
Section: Introductionunclassified